The plant world of the Khorassan-Kopet Dagh Floristic Province: A tribute to Eskandar Firouz - Sennikov, Alexander N. (Phytotaxa, 2016)
The current issue of Phytotaxa includes contributions of Prof. Hossein Akhani and his team of Iranian botanists on the flora of the Khorassan-Kopet Dagh Floristic Province, Iran. This book is a continuation of the long-term studies of these botanists on the flora of northeastern Iran, once culminated in a series of publications devoted to the flora of the Golestan National Park (Akhani 1998, 2005).